PENTINGNYA AKLIMATISASI PANAS PADA PELARI REKREASIONAL: MANFAAT, TANTANGAN, DAN STRATEGINYA - Fritzie Azalia Faustine; Irmayani Rahman; Reggina Maulidiana Tasya; Ainun Jihaan Nauli Pulungan; Aurick Athallah Padraya; Erica Kholinne (Jurnal Akta Trimedika, 2025)
Exertional heat illness (EHI) is the leading cause of death in young athletes each year, especially for competitive, recreational and tactical athletes. Exertional heat stroke (EHS), the most severe form of EHI, continues to have a high mortality rate, with mortality rates in 2002-2011 higher than any previous decade in the last four decades. This risk is even greater for recreational runners in Indonesia who train under a hot and humid tropical climate. To overcome this challenge, heat acclimatization is an important physiological adaptation method in preventing heat illness during exercise. Heat acclimatization improves the body's ability to thermoregulate, including cardiovascular efficiency, increased blood plasma volume and better core temperature regulation, reducing the risk of heat-related disorders. It also increases sweat sensitivity and rate for more effective cooling, optimizes muscle energy use, and improves thermal comfort and physical endurance. According to Beat The Heat in World Athletic Road Races, the acclimatization strategy includes adaptation two weeks prior to competition, plus weekly repetition sessions during training, or pre-departure acclimatization continued one week after arrival at the competition site. This method aims to optimize the body's readiness for extreme heat conditions, reduce the risk of EHI, and improve performance in competition.